Adsorption characteristics of ferro -fol drug with bentonite clay, kinetic and thermodynamic studies (مجلة ديالى للبحوث الانسانية, 2022)
A batch adsorption system was applied to study the adsorption of different concentration from Fe (11) from aqueous solution by bentonite clay at temperature range (303-323) K.The adsorption capacities and rate of Fe (11) ions on to clay were evaluated. Langmuir and freundlich adsorption models were applied to describe the isotherms and isotherm constants.Equilibrium data agreed very well with the Langmuir model.The kinetic experiment data correlated well with the first order kinetic model using Lagergreen's equation, Thermodynamic parameters for the sorption process was studied. Results also showed that bentonite was favourable adsorbed.